Resource use, characteristics and outcomes of prolonged non-invasive ventilation: a single-centre observational study in China. Issue 12 (4th December 2018) - Duan, Jun; Bai, Linfu; Zhou, Lintong; Han, Xiaoli; Jiang, Lei; Huang, Shicong
Abstract : Objective: To report the resource use, characteristics and outcomes of patients with prolonged non-invasive ventilation (NIV). Design: A single-centre observational study. Setting: An intensive care unit of a teaching hospital. Participants: Patients who only received NIV because of acute respiratory failure were enrolled. Prolonged NIV was defined as subjects who received NIV ≥14 days. A total of 1539 subjects were enrolled in this study; 69 (4.5%) underwent prolonged NIV. Main outcome measures: Predictors of prolonged NIV and hospital mortality. Results: The rate of do-not-intubate (DNI) orders was 9.1% (140/1539). At the beginning of NIV, a DNI order (OR 3.95, 95% CI 2.25 to 6.95) and pH ≥7.35 (2.20, 1.27 to 3.82) were independently associated with prolonged NIV. At days 1 and 7 of NIV, heart rate (1.01 (1.00 to 1.03) and 1.02 (1.00 to 1.03], respectively) and PaO2 /FiO2 <150 (2.19 (1.25 to 3.85) and 2.05 (1.04 to 4.04], respectively) were other independent risk factors for prolonged NIV. When patients who died after starting NIV but prior to 14 days were excluded, the association was strengthened. Regarding resource use, 77.1% of subjects received NIV<7 days and only accounted for 47.0% of NIV-days. However, 18.4% of subjects received NIV 7–13.9 days and accounted for 33.4% of NIV-days, 2.9% of subjects received NIV 14–20.9 days and accounted for 9.5% of NIV-days, and 1.6% of subjects received NIV≥21 days and accounted for 10.1% of NIV-days. Conclusions: Our results indicate the resource use, characteristics and outcomes of a prolonged NIV population with a relatively high proportion of DNI orders. Subjects with prolonged NIV make up a high proportion of NIV-days and are at high risk for in-hospital mortality.